Sec22b determines Weibel-Palade body length by controlling anterograde endoplasmic reticulum-Golgi transport - Karampini, Ellie (Haematologica, 2020)
Von Willebrand factor (VWF) is a multimeric hemostatic protein that is synthesized in endothelial cells, where it is stored for secretion in elongated secretory organelles called Weibel-Palade bodies (WPB). The hemostatic activity of VWF is strongly related to the length of these bodies, but how endothelial cells control the dimensions of their WPB is unclear. In this study, using a targeted short hairpin RNA screen, we identified longin-SNARE Sec22b as a novel determinant of WPB size and VWF trafficking. We found that Sec22b depletion resulted in loss of the typically elongated WPB morphology together with disintegration of the Golgi and dilation of rough endoplasmic reticulum cisternae. This was accompanied by reduced proteolytic processing of VWF, accumulation of VWF in the dilated rough endoplasmic reticulum and reduced basal and stimulated VWF secretion. Our data demonstrate that the elongation of WPB, and thus adhesive activity of their cargo VWF, is determined by the rate of anterograde transport between endoplasmic reticulum and Golgi, which depends on Sec22b-containing SNARE complexes.